2020
DOI: 10.1097/md.0000000000022152
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus in women increased the risk of neonatal infection via inflammation and autophagy in the placenta

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 52 publications
0
37
1
1
Order By: Relevance
“…There was also a significantly higher BMI and incidence of GDM in the FIRS group than in the non‐FIRS group. The risk of GDM was positively associated with the pre‐pregnancy BMI, 23 and GDM led to an increase in the risk of intrauterine infection 24 …”
Section: Discussionmentioning
confidence: 97%
“…There was also a significantly higher BMI and incidence of GDM in the FIRS group than in the non‐FIRS group. The risk of GDM was positively associated with the pre‐pregnancy BMI, 23 and GDM led to an increase in the risk of intrauterine infection 24 …”
Section: Discussionmentioning
confidence: 97%
“…50 In contrast, Li et al examined cohorts of 22 pregnant patients with GDM compared to 28 pregnant patients without DM to investigate differences in growth parameters, placental changes including weight and inflammation, and neonatal outcomes. 51 The authors found that patients with a first-time diagnosis of GDM gave birth to neonates with higher rates of neonatal morbidity, including infection (18.1% in GDM vs. 0% in those without DM, P < .05) and hyperbilirubinemia (27.2% in GDM vs. 3.6% without DM, P < .05). 51 When they examined differences in inflammation between pregnant persons with GDM or without, they found significantly higher levels of inflammatory cytokines IL-6 and IL-8 in the gestating parent and cord blood (P < .05).…”
Section: Neonatal Infections Of Infants Exposed To Dm In Uteromentioning
confidence: 97%
“…51 The authors found that patients with a first-time diagnosis of GDM gave birth to neonates with higher rates of neonatal morbidity, including infection (18.1% in GDM vs. 0% in those without DM, P < .05) and hyperbilirubinemia (27.2% in GDM vs. 3.6% without DM, P < .05). 51 When they examined differences in inflammation between pregnant persons with GDM or without, they found significantly higher levels of inflammatory cytokines IL-6 and IL-8 in the gestating parent and cord blood (P < .05). 51 However, limitations of their study included a small sample size (∼50 pregnant patients), lack of consistency in defining neonatal infection, and exclusion of patients with chorioamnionitis and/or preterm rupture of membranes.…”
Section: Neonatal Infections Of Infants Exposed To Dm In Uteromentioning
confidence: 97%
See 1 more Smart Citation
“…Gestational diabetes mellitus (GDM) is the most common endocrine disease in pregnancy and, by definition, refers to diabetes mellitus disease first diagnosed during pregnancy (1)(2)(3)(4). In a normal pregnancy, some physiological changes, such as hyperinsulinemia, increased insulin sensitivity, and mild postprandial hyperglycemia, occur to meet the increasing needs of the mother and the baby, especially after the second trimester (5,6). If the patient's glucose metabolism before pregnancy is normal, the development of GDM stems from metabolic dysfunction (7,8).…”
Section: Introductionmentioning
confidence: 99%